A Case of Primary Subglottic Malignant Melanoma with a Successful Surgical Treatment - Shahzad Ahmad; Mahmoud Abdelghany; Curtis Goldblatt; Owen Stark; Nicholas Masciotra (Case Reports in Oncological Medicine)
Primary subglottic malignant melanoma is a very rare and underdiagnosed neoplasm. We are reporting a case of primary malignant melanoma of subglottic mucosa in a 78-year-old woman who presented to our hospital with shortness of breath and hoarseness of voice. Laryngoscopy and excisional biopsy along with immunoreactivity to S-100 and human melanoma black-45 (HMB-45) confirmed the diagnosis. The patient was treated with laryngectomy followed by radiotherapy. Five years following surgical treatment, she continues to be asymptomatic. To our knowledge, there is only one reported case of primary malignant melanoma of subglottic mucosa in the medical literatures.